The Influence of Leadership and Compensation on Testing Service achievement with Work Motivation as an Intervening Variable (Case research at the General Service Agency of the Center for Standardization and Industrial Service in Bogor) - Zulkarnain, Mardlo; Ahmad Badawi Saluy; Novawiguna Kemalasari (Dinasti Publisher, 2024)
Utilizing leadership, compensation, and motivation as intermediary variables, this research seeks to enhance the achievement of testing service personnel at the Center for Standardization and Industrial Services. A quantitative method is utilized in this investigation. Quantitative research is a positivist-based approach to researching populations or samples, with the goal of testing hypotheses via the use of research instruments and quantitative/statistical data analysis. The following outcomes are derived from the research and data analysis conducted; 1) The assessment services achievement at BBSPJI in Bogor is positively and insignificantly affected by leadership. At BBSPJI in Bogor, testing service achievement is positively and insignificantly affected by compensation. 3) The impact of leadership on motivation is both good and substantial. 4) There is a small but favourable impact of compensation on motivation. 5) The testing services at BBSPJI in Bogor are significantly and positively impacted by motivation. 6) utilizing motivation as an intermediary variable, leadership at BBSPJI in Bogor has a favourable and considerable impact on the achievement of testing services. 7) utilizing incentive as a moderating variable, compensation has a small but favourable impact on testing service achievement at BBSPJI in Bogor.